A Trajectory Tracking FLC Tuned with PSO for Triga Mark-II Nuclear Research Reactor - (:unkn) unknown (SPRINGER, 2011)
In this study, a Partial Swarm Optimization tuning Trajectory Tracking Fuzzy Logic Controller (PSO-TTFLC) is designed for the nuclear research reactor Triga Mark-II in Istanbul Technical University (ITU). Reason to use TTFLC as a controller is that it uses only the error and error derivative as input parameters. TTFLC provides to work with the PSO algorithm. For this reason required changes are made in designed controller. Weights of the rules in rule base of the fuzzy controller are provided by the PSO. These parameters optimized by PSO are used to control the reactor for several working condition. Performance of the designed PSO-TTFLC is tested for various initial and desired power levels. The simulation results show that the reactor power successfully tracks the given trajectory and reaches the desired power level with the optimized weights of rules. As a result, PSO-TTFLC could control the system successfully under all conditions within the acceptable error tolerance.
Keywords: PSO; Fuzzy logic control; Trajectory tracking; Nuclear reactor control; FUZZY-LOGIC CONTROLLER; OUTPUT